Hemophagocytic lymphohistiocytosis in gastric cancer: A rare syndrome for the oncologist. Case report and brief review - Monti, Manlio; Marconi, Giovanni; Ambrosini-Spaltro, Andrea; Gallio, Chiara; Ghini, Virginia; Esposito, Luca; Antonini, Stefano; Montanari, Daniela; Frassineti, Giovanni Luca (Frontiers in Oncology, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening condition characterized by uncontrolled activation of the immune system. HLH is a reactive mononuclear phagocytic response that occurs in association with a constellation of conditions such as malignancies and infections. The clinical diagnosis of HLH remains challenging because HLH can present with symptoms that significantly overlap with other causes of cytopenia, such as sepsis, autoimmune diseases, hematological cancers, and multiorgan failure. A 50-year-old man went to the emergency room (ER) for hyperchromic urine, melena, gingivorrhagia and spontaneous abdominal wall hematomas. The first blood tests showed severe thrombocytopenia, alteration of the INR and consumption of fibrinogen and therefore, a diagnosis of disseminated intravascular coagulation (DIC) was made. A bone marrow aspirate showed numerous images of hemophagocytosis. With the suspicion of immune-mediated cytopenia, oral etoposide, intravenous immunoglobulin, and intravenous methylprednisolone were administered. Then a diagnosis of gastric carcinoma was performed on a lymph node biopsy and by gastroscopy. On the thirtieth day, the patient was transferred to the oncology ward of another hospital. On admission, he had serious piastrinopenia, anemia, hypertriglyceridemia and hyperferritinemia. He was supported with a platelet transfusion and underwent a bone biopsy that showed a picture compatible with myelophthisis from diffuse medullary localization of a carcinoma of gastric origin. A diagnosis of HLH secondary to solid neoplasm was formulated. The patient started chemotherapy with oxaliplatin, calcium levofolinate, 5-fluorouracil bolus, 5-fluorouracil 48 hours (mFOLFOX6) and methylprednisolone. Six days after the third cycle of mFOLFOX6, the patient was discharged with stabilization of his piastrinopenia condition. The patient continued chemotherapy with improvement of clinical conditions and normalization of hematological values. After 12 cycles of mFOLFOX it was decided to start maintenance chemotherapy with capecitabine but, unfortunately, after only one cycle HLH reappeared. The oncologist has to keep in mind the existence of HLH when there is an unusual clinical presentation of cancer, such as cytopenia affecting ≥2 lineages and alterations of ferritin and triglycerides other than fibrinogen and coagulation. Increased attention and additional research as well as a close collaboration with hematologists are needed to benefit patients with solid tumors complicated by HLH.